IMPLEMENTATION OF ACADEMIC FREEDOM POLICY IN LAW NUMBER 12 OF 2012 ON HIGHER EDUCATION - Agus Supriyanto; Gunawan Widjaja (Adisam Publisher, 2025)
Academic freedom is an essential part of human rights, manifested in the freedom of thought and expression in the context of higher education. Law No. 12 of 2012 on Higher Education explicitly regulates academic freedom as a right and obligation of the academic community in carrying out the three pillars of higher education. This study aims to examine how academic freedom policies are implemented in higher education institutions, particularly in the conduct of research, teaching, and academic freedom of speech, as well as the challenges faced during the implementation of these policies. The method used is juridical-normative with a qualitative approach through a study of relevant laws, policy documents, and academic literature. The results of the study indicate that academic freedom must be protected and facilitated by higher education leaders so that the academic community can develop knowledge responsibly in accordance with legal norms and academic ethics. However, there are various restrictions and challenges in practice that need attention to strengthen the implementation of academic freedom policies in the future.